Kesan Perantara Kepuasan, Kepercayaan, dan Komitmen pada Hubungan Antara Kualiti Perkhidmatan dan Kesetiaan Pelanggan pada Bank Islam - Parawansa, Dian Anggraece Sigit (2013)
This study seeks to examine and analyze the impact of service quality and customer loyalty on trust, satisfaction, and commitment to customers. Specifically, the objective of this study is to design a measurement tool for service quality in Islamic Banks. In addition, the pattern of interactions among service quality, trust, satisfaction, commitment, and customer loyalty within the Islamic Banks is also within the high concern. In accordance, questionnaires were used to collect data. This enables the study to gather data directly from respondents. In overall, a total of 384 questionnaires have been distributed to customers of Bank Shariah (Islamic Commercial Banks) and Business Unit Shariah (Islamic Business Unit). Of the total, 350 (91.14 percent) of the complete questionnaire was used for data analysis. The gathered data were analyzed using Structural Equation Modeling (SEM) and SPSS statistical software version 19 and AMOS version 18.0. In the end, the results show that service quality, trust, satisfaction, and commitment have significant impacts on customer loyalty at 95 percent confidence level. In addition, the results also reveal that trust, satisfaction, and commitment have significant impacts on the relationship between service quality and customer loyalty to the Islamic Banks. This shows a clear trend that the better the quality of service provided to the customers then the customer will continuously believe and trust to keep patronizing Islamic Banks. Trust, customer satisfaction, and commitment can be an intervening variable in the relationship between service quality and customer loyalty, particularly in an environment of Islamic banking services and general services industries. Thus, these estimates can be used to be part of the marketing strategy in order to enhance and add value to its services in serving customers